Formação de professores de educação infantil : para que? - Faria, Marilia de Sousa Castelo Branco (2007)
This paper talked about the formation of teachers from the children`s education having as base my performance as educational supervisor on a program children in the nursery from the municipal foundation of education from ´´Niterói``. I have carried out an investigation considering the following issues: What are the conception that the teachers of children`s education have related to these stages of education? What are your conception related to the function of community nursery? What are your conceptions about the childhood? And, what they think about your own function as teachers of children`s education from the community nursery with agreement to the municipal foundation of education from Niterói. This study had as theoretical support, the critical theory from the society, with emphasis on the thought of Theodor Adorno, whose conceive the education as space of clarify the independence, contributing this way, for the critical reflexion that I carried out in the study, arguing about the formation of teachers that for now present themselves in one capitalist society (under the ´´Neoliberal Paradigma`` ) and that objectivs the social adaptation from the individual ignoring your process of building the autonomy and development of sensibility aspects those, according to Adorno, must be developed on the first chldhood and are looking forward to the question that gives the titles to this study. Seven teachers where interviewed from the community nursery, having an agreement with the municipal foundation of education from Niterói, through the chldren in the nursery program. The analysis of datas, taken in the interviews semi-structured, identified practices that disassociate the actions to care and educate, fundamental and indisociable, on the work with the children`s education. In concern to the childhood, it was verified that still persists the idea much deep-rooted from the children seen as an images from is missing and not as na historical person and grifted of emotions. It was still verified, principles of maternity in the conception of your function as teacher of children`s education on what, there are, moments of work with the child, na what to take care comes over to educate. However, I consider that these thoughts are processual and are modifing along the history of children s education, with bases on the dialogue with its conceptions about the childhood, the institution and your own function as educator, contributing for your location and Professional consolidation.